Adaptation of the spiders to the environment: the case of some Chilean species - Canals, Mauricio; Veloso, Claudio; Solís, Rigoberto (Frontiers in Physiology, 2015)
Spiders are small arthropods that have colonized terrestrial environments. These impose three main problems: i) terrestrial habitats have large fluctuations in temperature and humidity; ii) the internal concentration of water is higher than the external environment in spiders, which exposes them continually to water loss; and iii) their small body size determines a large surface / volume ratio, affecting energy exchange and influencing the life strategy. In this review we focus on body design, energetic, thermal selection, and water balance characteristics of some spider species present in Chile and correlate our results with ecological and behavioral information. Preferred temperatures and critical temperatures of Chilean spiders vary among species and individuals and may be adjusted by phenotypic plasticity. For example in the mygalomorph high-altitude spider Paraphysa parvula the preferred temperature is similar to that of the lowland spider Grammostola rosea; but while P. parvula shows phenotypic plasticity, G. rosea does not. The araneomorph spiders Loxosceles laeta and Scytodes globula have greater daily variations in preferred temperatures at twilight and during the night, which are set to the nocturnal activity rhythms of these species. They also present acclimation of the minimum critical temperatures. Dysdera crocata has a low preferred temperature adjusted to its favorite prey, the woodlouse. Spider metabolic rate is low compared to other arthropods, which may be associated with its sit and wait predatory strategy particularly in primitive hunter and weavers. In mygalomorph spiders the respiratory system is highly optimized with high oxygen conductance, for example G. rosea needs only a difference of 0.12 to 0.16 kPa in the oxygen partial pressure across the air-hemolymph barrier to satisfy its resting oxygen consumption demands. Water loss is a significant stress for spiders. Paraphysa parvula shows an evaporative water loss ten times more than usual w